Visualization of pathologic changes in liver tissue via polarized light - Stoilova, Ani; Blagoeva, Blaga; Nazarova, Dimana; Stoykova, Elena; Berberova-Buhova, Nataliya; Nedelchev, Lian; Machikhin, Alexander (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In this work, we applied two polarized light based approaches to visualize histological patterns of liver pathologies. The first one involves acquisition of two images through a polarizing microscope, one image (Ppar) acquired with the analyzer oriented parallel to the polarization of illumination and the other (Pper) acquired with the analyzer oriented perpendicular to the illumination. The final image is based on the polarization ratio, Preconstructed = (Ppar – Pper)/(Ppar + Pper). Using the second technique, the histological specimens were illuminated with a polarized laser beam with wavelength of 635 nm. Polarimetric parameters as azimuth, angle of ellipticity, degree of polarization and reflected power have been measured to quantify the change in the polarization state of the incident light after interaction with the sample of the healthy tissue and of the tissue with abnormal morphological changes.
Optica Applicata, Vol. 52, 2022, nr 3, s. 395-404
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; polarized light imaging; tissue polarimetry; liver tissue